Smart Fertilizers and Innovative Organic Amendments for Sustainable Agricultural Systems - de la Luz Mora, Maria; Rumpel, Cornelia; Calabi-Floody, Marcela (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Sustainable agricultural practices are needed to provide food security for a growing global population. Food production is usually associated with high nutrient inputs in the form of mineral fertilizers. Since the beginning of agriculture, such practices have led to soil degradation and the release of environmental contaminants. In this Special Issue, we will focus on innovations in organic and inorganic fertilizer production. We welcome studies concerning new approaches for smart fertilizer development, including bioformulations with mineral particles, nanomaterials, and plant growth promoting microorganisms. We especially encourage authors taking advantage of ecological interactions to improve plant nutrient-use efficiency. Moreover, we would like to include contributions that focus on organic amendments to increase or propitiate the terrestrial C sequestration and stabilization, in order to contribute to mitigating climate change at the same time increasing food security by soil fertility, thus making win-win-win scenarios. Such techniques may concern, but are not limited to, innovative organic waste recycling procedures and new applications of mycorrhizae, rhizobioms, or free living soil bacteria and fungi.